THE COMPARATIVE ANALYSIS OF THE SOIL INVERTEBRATES COMMUNITIES (MACROFAUNA) ON VIRGIN AND CULTIVATED LANDS OF KOSTANAY DISTRICT, KOSTANAY REGION - Bragina, T.M.; Bragin, E.A.; Bobrenko, M.A.; Rulyova, М.М. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
The soil population (macrofauna) is a good indicator of the ecological status of the ecosystem. Large soil invertebrates are sensitive to changes in the chemical and physical properties of soils, the reaction of soil solutions, which leads to changes in their population structure, abundance, and biomass. The pu-rpose of this work is to analyze changes in the population structure of soil inver-tebrates (macrofauna) under the influence of prolonged plowing and fallowing of agricultural lands in conditions of southern black soil (chernozem) on loams. The material was collected using the method of soil and zoological samples. The com-position and the population density of the macrofauna in the virgin land and agri-cultural clean cultivation fields were analyzed. Changes in the population structure on the virgin plot and on agricultural land with different modes of use are noted.
Keywords: soil invertebrate; macrofauna; southern black soil (cherno-zem); Kostanay region; virgin steppe; clean cultivation